The origins of Huanca as a cult object in pre-colonial times - Falcón Huayta, Víctor (2004)
Possibly, from the earliest times, societies have tried to organize the environment and explain it through formulas that were originally born from magic. Celestial and telluric phenomena, as well as everyday events, had their justification in beliefs linked to the supernatural or to an alternative reality, whose events were not under the direct will of man who, however, could channel them in some way through ritual. and propriety. These worldviews tried to contemplate reality and its different facets under a single explanatory system and in its entirety.